Overlay cognitive transmission in OFDM point to point systems exploiting primary feedback - Alberto Rico-Alvariño; C. Mosquera (3rd International Workshop on Cognitive Information Processing (CIP), 2012)
A secondary user that tries to reuse the spectrum allocated to a primary user can exploit the knowledge of the primary message to perform this task. In particular, the overlay  cognitive radio paradigm postulates the use of a fraction of the available power at the secondary transmitter to convey the primary message, so the spectral efficiency of the primary  system is increased, and, therefore, some transmission resources (time slots or frequency bands) can be released to the secondary transmission while the primary user rate is kept constant. The fraction of released resources can be incremented if some channel state information is available at the secondary transmitter. In this paper, we present a scenario where the secondary transmitter maximizes the primary link quality (measured in terms of Effective SNR), and obtains its channel state information by exploiting the primary user SNR-based feedback.
Keywords: cognitive radio; dynacs